LOCAL WISDOM: A SOLUTIONTO SURPASSHEDONISMEFFECTS ONENVIRONMENTPOLLUTION - Armaidy Armawi (Indonesian Journal of Geography, 2010)
Science and technology on modern human create dualism result whichcomplete opposite. Those results are as proper instrument to fulfill increasinglycomplex of human needand as nature exploltatlon instrument with dehumanizationas result and also the trap of historical ratlona/lty. The hedonism ethics trend has asignificant role on the second result. It means, whether the hedonism terminologyis /lmlted with "lust" meaning which .refer to ego existence. Therefore the naturewill define as "phallus" which will explolt freely as the exploitation subject tofulfill the lust, and the heavy pollution on environment is unavoidable. Thishistorical ratlona/lty should be cut as an effort to save thefuture. Local wisdom isa promising therapy alternative. Local wisdom has universal values to return to thenature path,' namely ethical values with natura magistrate prlnclpal on interaction,interrelation and interdependency relation between human and nature. Only thlsharmony will able to maintenance the sustainable environmental protection to thefuture.